An Overview on Neonatal Acute Kidney Injury: A Case Study from Tertiary Care Hospital in Jammu and Kashmir, India - Mohammad Ashraf (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter aimed to know the incidence rate of AKI and its associated risk factors among the NICU patients to depict the disease burden and its impact. Acute kidney injury (AKI) is a clinical syndrome that complicates the course and worsens the outcome in a significant number of hospitalised patients. Recent advances in clinical and basic research will help with a more accurate definition of this syndrome and in the elucidation of its pathogenesis. Neonates who suffer hypoxic ischemic encephalopathy often develop multiorgan failure, which impacts virtually every organ system. The findings suggest that the incidence of neonatal AKI would have been even higher if more rigorous AKI surveillance protocols were implemented. The most common cause for neonatal admission in our NICU was perinatal asphyxia followed by neonatal sepsis. The findings are limited by our definition of AKI, which relies on SCr changes to diagnose AKI in addition to the fact that we did not take urine output as a marker of AKI.